Crowdsourced Measurement of Reaction Times to Audiovisual Stimuli With Various Degrees of Asynchrony. (December 2018) - Bazilinskyy, Pavlo; Winter, Joost de
Objective: This study was designed to replicate past research concerning reaction times to audiovisual stimuli with different stimulus onset asynchrony (SOA) using a large sample of crowdsourcing respondents. Background: Research has shown that reaction times are fastest when an auditory and a visual stimulus are presented simultaneously and that SOA causes an increase in reaction time, this increase being dependent on stimulus intensity. Research on audiovisual SOA has been conducted with small numbers of participants. Method: Participants ( N = 1, 823) each performed 176 reaction time trials consisting of 29 SOA levels and three visual intensity levels, using CrowdFlower, with a compensation of US$0.20 per participant. Results were verified with a local Web-in-lab study ( N = 34). Results: The results replicated past research, with a V shape of mean reaction time as a function of SOA, the V shape being stronger for lower-intensity visual stimuli. The level of SOA affected mainly the right side of the reaction time distribution, whereas the fastest 5% was hardly affected. The variability of reaction times was higher for the crowdsourcing study than for the Web-in-lab study. Conclusion: Crowdsourcing is a promising medium for reaction time research that involves small temporal differences in stimulus presentation. The observed effects of SOA can be explained by an independent-channels mechanism and also by some participants not perceiving the auditory or visual stimulus, hardware variability, misinterpretation of the task instructions, or lapses in attention. Application: The obtained knowledge on the distribution of reaction times may benefit the design of warning systems.